1866 Mass. Acts 219 - (:unkn) unknown (My University, 1866)
An Act Concerning The Militia, § 184: "Section 184. It shall not be lawful for any body of men whatsoever, other than the regularly organized corps of the volunteer militia, the troops of the United States, and the ancient and honorable artillery company, and the veteran artillery association of Newburyport, to associate themselves together as a military company or organization, or to parade in public with arms in any city or town of this Commonwealth, without the license of the governor thereof, which may at any time be revoked;§
Keywords: MILITIAS